PENGARUH MODEL PEMBELAJARAN DAN BELIEF MATEMATIKA TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS - Lely Lailatus Syarifah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2016)
ABSTRACT: This study aims to determine the effect of learning model learning cycle and direct learning and mathematical belief in the ability of mathematical communications with quasi-experimental method and 2 x 2 factorial design treatment by level. Retrieving data using mathematical communication test instruments and mathematical belief questionnaire. The study population was the eighth grades students of SMPN in Tangerang on the Academic Year 2014/2015. Samples were taken by multistage random sampling technique. Analysis techniques using two-way ANOVA. The results showed that: 1) The ability to communicate mathematical students treated learning model learning cycle is higher than the direct learning, 2) There is an interaction effect between learning model belief mathematics to mathematical communication, 3) ability to communicate mathematical students treated learning model of learning cycle is higher compared to the treated directly on the learning group of students who have high math belief, 4) There is no difference in the ability of communication in the group of students who have low math belief. Keyword: Belief, Mathematical communications, Learning model